Experimental Investigation on Dew Point Indirect Evaporative Cooling System Combined with Mechanical Refrigeration for Data Center - He Hongxia; Huang Xiang; He Huaming; Chu Junjie; Sun Tiezhu (Zhileng xuebao)
To reduce the energy consumption of air conditioning and improve heat exchange efficiency in data center, this paper proposes a composite air conditioning system combined dew-point indirect evaporative cooling, which involves a combination of counter-flow and cross-flow heat exchangers, with mechanical refrigeration. A test bench was built for the composite air conditioning system, and the system performances under dry conditions and high-humidity conditions with return air temperatures of 26 ℃ and 35 ℃were tested. The experimental results show that: (1) In the wet mode, when the return air temperature is lower than 26 ℃, the maximum wet-bulb efficiency of the unit under dry conditions is 97%; when the return air temperature of the simulated data center is higher than 35 ℃, the wet-bulb efficiency of the unit under dry conditions is approximately 110%, and the wet-bulb efficiency of the unit under high-humidity conditions is also 99%; (2) In the mixed mode, the wet-bulb efficiency of the dew-point indirect evaporative cooler under dry conditions and high-humidity conditions is approximately 120% and 110% respectively. The test results show that the dew-point indirect evaporative cooling technology is more suitable in dry areas, and auxiliary mechanical refrigeration is required in medium- and high-humidity areas. In particular, when the return air temperature is low, the effect of evaporative cooling under high-humidity conditions is limited and the auxiliary mechanical refrigeration is needed to meet the air supply requirements. When the return air temperature is high, evaporative cooling can reduce the time required for mechanical refrigeration.